THE EFFECT OF AL-THARTHAR-EUPHRATES CANAL ON THE QUANTITATIVE AND QUALITATIVE COMPOSITION OF ZOOPLANKTON IN EUPHRATES RIVER - Rabee, Adel M (Al-Nahrain Journal of Science, 2010)
phrates canal, while the remaining two were located at Euphrates River, to know the effect ofAl-Tharthar-Euphrates canal on the composition and diversity of zooplankton in Euphrates River.In all the studied stations the total zooplankton showed high densities in autumn and low densitiesin summer. The statistical analysis results showed significant difference between station 3 andstation 4 in Euphrates River. Rotifera were the dominant group quantitatively, followed byCopepoda and Cladocera. 52 taxa of zooplankton were recorded, 32 taxa belonged to Rotifera, 12 tothe Cladocera and 7 to the Copepoda. The results also showed that the Rotifera: Keratellacochlearis and Brachionus calyciflours, the Cladocera: Bosmina longirostris, the Copepoda: naupliiwere dominant in both canal and Euphrates River. The biodiversity indices indicated highfluctuated with seasons. The results also showed that the species composition in the Euphrates riverwere not affected by the canal water. The higher values of uniformity index of differentzooplankton groups indicate there is no ecological stress on zooplankton in the study area.NON